A study on knowledge of information commodity based business amongst Bumiputera entrepreneur / Nora'ayu Binti Ahmad Uzir, Irni Eliana Binti Khairuddin and Prof. Madya Dr. Norliya Binti Ahmad Kassim - Ahmad Uzir, Nora'ayu; Khairuddin, Irni Eliana; Ahmad Kassim, Norliya (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2012)
The entrepreneurs are the influential force that makes the business world dynamic. The development of entrepreneurship has been growing in importance in Malaysia. The perceived importance of entrepreneurship to the growth of Malaysia's economy is evidenced by the sheer amount and variety of supporting mechanisms and policies that exist for entrepreneurs, including funding, physical infrastructure and business advisory services. Considered as one of the growth engines for a nation - creating jobs, inventions and diversity, entrepreneurship is a process of starting a business venture, organizing the necessary resources and assuming the associated risks and rewards (Firdaus, et al., 2009). There have been several studies which define meaning of entrepreneurship.